Fluorescence correlation spectroscopy studies of diffusion in and over nanostructured soft and hard materials - Shafiee, Omid (Kansas State University, 2024)
This dissertation explores mass transport of molecules confined within soft and hard nanostructures, by employing the method of fluorescence correlation spectroscopy (FCS). FCS is a single molecule spectroscopy method that allows for the study of diffusion by fluorescent molecules one at a time. Lyotropic liquid crystals (LLCs) made from C₁₂EO₁₀ surfactants comprised the soft matter nanostructures explored in this dissertation. The hard matter nanostructures included nanoporous anodic aluminum oxide (AAO) membranes and polyethylene terephthalate (PET) microplastic surfaces, respectively. Nile red (NR) and Rhodamine B (RhB) were two fluorescent probes that were used in these studies. In the first study, solute diffusion within LLC gels prepared from a series of water and decaethylene glycol monododecyl ether (C₁₂EO₁₀) mixtures was explored using variable area fluorescence correlation spectroscopy (va-FCS). Aqueous C₁₂EO₁₀ gels were prepared in concentrations ranging from 55:45 to 70:30 wt% surfactant to water. Three different NR dyes were employed as model solutes. Each was separately doped into the LLC gels at nanomolar concentrations. Included were a hydrophilic form of NR incorporating an anionic sulfonate group (NRSO₃⁻), a hydrophobic form with a fourteen-carbon alkane tail (NRC₁₄), and the commercial NR as an intermediate case. FCS data acquired from the gels showed that NRSO₃⁻ diffused primarily in three dimensions, with its diffusion coefficient decreasing monotonically as gel concentration and micelle packing density increased. This behavior is consistent with the confinement of NRSO₃⁻ by exclusion from the micelle cores. NRC₁₄ exhibited the smallest diffusion coefficient, likely due to its larger size and enhanced interactions with the micelle cores. Commercial NR displayed an intermediate diffusion coefficient and the most anomalous behavior of the three dyes. The latter was attributed to its facile partitioning between core and corona regions of the micelles, and greater participation in one-dimensional diffusion. The results from these studies enhance our understanding of molecular mass transport through soft-matter nanomaterials, such as those being developed for drug delivery and membrane-based chemical separations. In the second study, FCS was utilized to investigate organic molecules adsorbed from aqueous solution onto the surfaces of synthetic secondary microplastics. Both fresh and artificially aged PET plastics were employed. The plastics were artificially aged in a UV-ozone chamber. Raman and infrared spectra confirmed the composition of the PET microplastics. Water contact angle and surface roughness measurements revealed an increase in wettability and surface roughness with aging, consistent with oxidation of the plastic surface. Rhodamine B dye was used as a fluorescent probe in FCS studies and served as an analogue for organic pollutants commonly found on microplastics. The FCS results revealed the accumulation of dye on the PET surfaces as they were aged. Dye motion was significantly slower on the plastics than in bulk aqueous solution and occurred by anomalous sub diffusion. The rate of diffusion became dramatically slower and more anomalous as the plastics were aged. Surface diffusion is likely slowed by either ionic interactions or hydrogen bonding between the dye and plastic. These results provide new insights critical to understanding how microplastics accumulate and transport organic pollutants as they weather in the environment. In the third study, the diffusion of NR doped toluene-ethanol mixtures confined within 10 nm and 20 nm AAO nanopores was investigated. The results showed two distinct diffusion components, characterized as fast and slow diffusion. The fast diffusion coefficient (Df) was attributed to molecules that pass through the cylindrical pores largely unimpeded. However, the Df values were consistently smaller than the bulk diffusion coefficient (Db), with further reduction observed in 10 nm pores compared to 20 nm pores. This reduction in diffusion coefficient is attributed to long range dipole-dipole interactions between the pore surface and NR molecules. Additionally, Df values were correlated with mixture composition, mirroring the trend observed for Db, thus reflecting their dependence on solution viscosity. The slow diffusion coefficient (Ds) values were markedly smaller than Df but also followed the viscosity-dependent trends in Db. The Ds values were more than one- and two-orders-of-magnitude smaller than Db for the 20 nm and 10 nm pores, respectively. The dramatic reduction in the rate of diffusion by the slow mechanism was attributed to adsorption of the dye to the pore surface by a hydrogen bonding mechanism. These findings contribute to a deeper understanding of diffusion through nanoporous structures and the effects of nanoconfinement. The knowledge gained will allow for optimization of the performance of nanomaterials being developed for use in chemical separation. This new knowledge will also afford an improved understanding of the role played by nanoconfinement in gas and oil production from nanoporous shale rocks.
Keywords: Fluorescence correlation spectroscopy; Diffusion